Contextualization of Augmented Reality Digital Module Instruction: Grounded Theory Study in Examining Van Hiele’s Level of Geometric Thinking - Faizah, Siti; Sa’dijah, Cholis; Anwar, Lathiful; ., Sudirman; Muslim, Ahmad Bukhori (Journal of Ecohumanism, 2024)
Van Hiele’s thinking level has an important role in understanding, interpreting, and determining the geometric thinking ability. However, the lack of technological products that can support Van Hiele’s improvement in thinking level is a challenge in itself. One of the tools that can help prospective teacher students to reach Van Hiele’s level of thinking is Augmented Reality technology. Therefore, this study aims to investigate Van Hiele’s level of thinking through the intervention of Augmented Reality Digital Module Instruction (ADMI) using grounded theory design. The participants involved in this study were one lecturer and ten prospective teacher students who experienced difficulties in improving the level of Van Hiele geometric thinking. The data collected through observation, tests, and interviews are analyzed qualitatively through the stages of open coding, axial coding, and selective coding. These research found that students who had difficulties in carrying out the first level of Van Hiele could use ADMI to overcome these difficulties; students can construct knowledge about 3D geometry; the success of students in completing the geometry test involves reasoning. This study emphasize that ADMI contributes to geometry learning because it can make it easier for students to reach the lowest level of Van Hiele.